Pelaksanaan Pelatihan Keterampilan Modern Dance di Blitz Dance Studio Padang - Huda, Nahdahtul; Jamna, Jamaris (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
This research is motivated by the existence of modern dance training activities in a community at Blitz Dance Studio Padang which aims to channel the talents and potential possessed by the participants. The Participants in this community are generally at the age of children and adolescents who have motivation and enthusiasm. This is based on the use of media and methods in training. This study aims to describe how the implementation of modern dance skills training at Blitz Dance Studio Padang. This type of research uses a qualitative approach with the case study method. The data sources of this research are trainers and modern dance participants, as well as participant parents. The Data collection techniques used are observation, interviews, and documentation. Qualitative data analysis used is data reduction, data presentation, and drawing conclusions. The validity of the data employed is an extension of participation, observation, and triangulation. The results of data analysis were found: the media for the implementation of modern dance training uses audio media, visual media, media objects, and computer media. The method of implementing modern dance training uses lecture, question and answer and discussion methods, demonstration methods, and simulation game methods. Evaluation of the implementation of training is carried out using diagnostic, formative, and selective assessments. Diagnostic assessment is carried out every training process and after completion of the training which aims to see the weaknesses in the participants. Selective assessment is carried out to make selections in forming a team. A formative assesment was performed at the end of the training program by the way a coach ordered the participants to repeat the modern dance movement. Researchers suggest that trainers may use and develop good media, methods, and evaluations in the training of modern dance to give participans the ability to master the modern dance training movement according to the goal they wish to achieve